Registered nurses' perceptions of having a calling to nursing: A mixed-method study - Kallio Hanna; Kangasniemi Mari; Hult Marja (WILEY, 2022)
Aim: To explore how nurses perceived having a calling to nursing.
Design: A mixed-method study.
Methods: Survey data collected in autumn 2020 and semi-structured individual interview data collected in spring 2021. The 7925 survey respondents were care professionals and 414 of them were registered nurses. The 23 interview participants were registered nurses who responded to the survey. We examined the survey results using analysis of variance and t-tests and the interview data with qualitative thematic analysis.
Results: Registered nurses had a lower calling than other care professionals. Based on the interviews, having a calling to nursing produce four key findings. Nurses with a calling experienced their work as meaningful. They also adopted a humane and holistic approach to their work. However, their calling could change during their professional career. Due to its historical roots, having a calling was seen as a risk for the nursing profession, as it meant nurses had an oppressed position in society and nurses associated it with poor working conditions and low pay.
Conclusion: Our study showed that having a calling to nursing had multidimensional benefits for the individual nurse, their patient, colleagues, organization and society, but showed strong association between calling and nurses' poor working conditions and low pay.
Impact: We found that nurses had a lower calling than other care professionals. Calling still exists, but it can produce tension in modern nursing. Organizations and society need to focus on how calling can be seen as a more positive attribute of nursing and improve nurses' working conditions and pay.